OBSERVATIONS ON THE BIOLOGY OF RACONDA RUSSELLIANA (GRAY) - Varghese, T J (Indian Journal of Fisheries, 2011)
Raconda russelliana (Gray) is a medium-sized clupeid fish found in the’Bay of Bengal to the Malay Archipelago’ (Day, 1878). It is commonlypresent in the catches from the mouth and fore-shore areas of the Hooghlyestuary. However, in this region fishing operations are restricted to thewinter months (mid-November to mid-February), for during other monthsfishing is practically impossible due to rough weather conditions. The fishcaught are generally sun-dried and consumed mostly by people of the lowincome group.